Analisis Relevansi Pembelajaran di SMPN 3 Darangdan dengan Kebutuhan Hidup Nyata Siswa Dalam Perspektif Filsafat Progressivisme - Ricky Yoseptry; Teten Nurtaufiqin; Puri Nuryani; Neneng Halimah (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2025)
Progressivism is an educational philosophy that emphasizes education being centered on students’ experiences in order to produce pragmatic and skilled graduates, rather than focusing on theoretical facts. This descriptive qualitative study aims to measure the relevance of learning at SMPN 3 Darangdan based on this framework. In conclusion, the school seeks to implement Progressivism by having teachers relate subject matter to local contexts and employ student-centered methods such as Project-Based Learning (PjBL) and Problem-Based Learning (PBL) to provide authentic learning experiences. Students perceive learning materials as relevant when they can be applied directly (such as in Crafts and practical Mathematics). However, implementation is constrained by structural factors (a dense curriculum and a culture focused on exam scores) and technical factors (limited teacher competence in designing authentic projects and inadequate facilities). For sustainability, strong structural support, enhancement of teacher competencies, and innovative leadership are required. This study employs a qualitative approach using a descriptive method, aiming to observe, analyze, and obtain a comprehensive overview of the relevance of learning at SMPN 3 Darangdan, Purwakarta Regency. SMPN 3 Darangdan has demonstrated a clear commitment to implementing relevant and experience-oriented learning in accordance with the principles of Progressivism. Teachers possess a solid philosophical understanding of curriculum relevance and strive to connect learning materials with students’ real-life contexts. Experience-centered learning, through methods such as Project-Based Learning and Problem-Based Learning, provides benefits for the development of academic competencies, social skills, and life skills. Nevertheless, implementation has not yet been fully stable due to structural barriers, limited facilities, and an educational culture that prioritizes exam scores. Continuous support from the school, improved teacher competence, and adequate facilities are needed so that progressive learning can be implemented more deeply and consistently.